Intelligent elderly care I - Koh, Kenneth Tong Jun (2015)
In this paper, the prototype of an intelligent elderly care system consisting of various intelligent agents will be presented. Each agents having its own functions will be working in a holistic manner to provide 24 hours monitoring on the elderly in a home environment without the intrusion of their privacy. By taking the ease of use into consideration, a light weight wearable sensor device was designed to be worn around the wrist of the elderly. This would not pose any restrictions to the movement of the elderly and hence allowing them to proceed on doing their usual daily activities with an ease of mind. Using an inertial measurement unit (IMU) which is embedded with a tri-axial accelerometer and an altimeter, the wireless sensor node worn around the wrist is able to provide movement monitoring on the elderly. Furthermore, by incorporating the GSM shield into this system, short-message-service (SMS) function was being implemented. Therefore, family members/caregivers were able to be notified promptly whenever a fall or a stationary condition was been detected by the IMU device. To get an accurate reading on the elderly indoor position at home, various sensor nodes were been placed at different locations around the house. They would continuously transmit received signal strength indicator (RSSI) values to the central processing unit which would then compute the data through the use of localization algorithms to estimate the position of the elderly. After which, all the data would be stored in a database server which could be remotely accessed through a user-oriented webpage which greatly increases the reliability of this platform. The operating principles of the intelligent elderly care prototype system will be discussed in detail with its feasibility in real-world situation been highlighted.